Regional Economic Outlook, April 2015 : Western Hemisphere Department: Northern Spring, Southern Chills. (Regional Economic Outlook, 2015)
The economic outlook for Latin America and the Caribbean remains very challenging. Regional growth is projected to decline for a fifth consecutive year in 2015, dipping below 1 percent. Weakness is concentrated among South America's commodity exporters, where falling global commodity prices have compounded country-specific challenges. Meanwhile, growth is projected to be steady or stronger for most of the Caribbean, Central America, and Mexico, supported by lower oil bills for importers and robust economic recovery in the United States. The analysis in this report examines core challenges facing the region: the impact of lower commodity prices on fiscal and external positions, the drivers of the slowdown in investment, and the role of economic diversification for longer-term growth prospects.